Gramsci's Concept of the "Simple": Religion, Common Sense, and the Philosophy of Praxis. Issue 4 (2nd October 2018) - Green, Marcus E.
Abstract : One of the minor yet recurring themes of Antonio Gramsci's Prison Notebooks is his treatment of the "simple, " a category he developed to examine the Catholic Church's paternalistic view of common people and peasants as "simple and sincere souls, " in contrast to its superior view of cultured intellectuals. Throughout the Notebooks, he examines how the Church's condescending and fatalistic portrayal of the "simple" provides a basis for common sense, reinforcing the conditions of subalternity. Because of the uncritical nature of common sense and the simple's desire for change, he argues for the articulation of a "renewed common sense" containing critical and reflective philosophical foundations that transcend the passivity and paternalism of religion. Such a movement requires defining and disseminating new conceptions of philosophy and culture that are critically grounded and provide a basis of struggle in which the "simple" play the predominant role in the direction of their political lives and in the creation of a new hegemony.